The Utilization of Used Cooking Oil Waste for Aromatherapy Candle in Laban Jaya Village, Citeupuseun, Lebak - Ahmad Rayhan; Dina Nur Mardiyah; Medina Masri (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2026)
Cooking oil consumption in Indonesia is relatively high, particularly in households and small-scale food businesses. Improper disposal of used cooking oil contributes to environmental pollution, whereas repeated reuse may pose health risks due to the formation of harmful compounds. Therefore, practical and community-based solutions are needed to promote safer and more sustainable waste management practices. This community service program aimed to enhance community knowledge and skills in utilizing used cooking oil as a raw material for producing value-added aromatherapy candles. The program was conducted in Laban Jaya Village, Citeupuseun, Lebak, through interactive educational sessions, hands-on training, and practical demonstrations. The implementation comprised three stages: preparation, implementation, and evaluation. Program effectiveness was assessed using a pre-test and post-test approach to measure participants’ understanding of the characteristics of used cooking oil, its environmental and health impacts, appropriate disposal methods, and the process of producing aromatherapy candles. The results showed a substantial increase in participants’ knowledge across all assessed indicators after the training activities. Participants were also able to follow and carry out the candle-making procedures effectively during the practical sessions. Overall, the program was implemented successfully, as indicated by active participant engagement and improved awareness of environmentally friendly waste management practices. The activity encouraged participants to use used cooking oil for non-food applications, thereby supporting environmental protection efforts and strengthening community capacity building through the development of practical skills with potential economic value.